An Approximation to Para leer al pato Donald: Between Intellectual History and Latin American Communication - Vahos, Yubely (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
This article is a reflection on the historical and intellectual conditions that made possible the writing of the book Para leer al pato Donald: comunicación de masa y colonialismo, by Ariel Dorfman y Armand Mattelart, as well as an assessment of its legacy in Latin American social thought. In it, the documentary research method is used, and the book is related to the theoretical contributions of intellectual history, the first Frankfurt School and the economic-political view of communication. This article argues that the validity of this work is based on the pioneering use that its authors made of concepts and methodologies, such as cultural imperialism and deconstructionism; It is also argued that is necessary to study Para leer al pato Donald in relation to the expectations and premises that encouraged its authors, to understand its contributions and gaps.